2022
DOI: 10.1126/sciadv.abn1440
|View full text |Cite
|
Sign up to set email alerts
|

Measles and Nipah virus assembly: Specific lipid binding drives matrix polymerization

Abstract: Measles virus, Nipah virus, and multiple other paramyxoviruses cause disease outbreaks in humans and animals worldwide. The paramyxovirus matrix (M) protein mediates virion assembly and budding from host cell membranes. M is thus a key target for antivirals, but few high-resolution structures of paramyxovirus M are available, and we lack the clear understanding of how viral M proteins interact with membrane lipids to mediate viral assembly and egress that is needed to guide antiviral design. Here, we reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 112 publications
0
21
0
Order By: Relevance
“…VP40 detachment from viral envelope is caused by a disruption of electrostatic interactions between VP40 and negatively charged lipids in the viral envelope, which have experimentally been demonstrated and attributed to a basic patch of lysine residues decorating the VP40 C-termini [48][49][50][51] . Considering that matrix protein assembly of other RNA viruses relies on electrostatic interactions with negatively charged lipids 60 , we propose that pH-mediated matrix disassembly is a general mechanism critical for viral uncoating. Notably, pH-driven structural remodeling of viruses has so far only been shown and extensively studied for influenza A virus 61 , which is known to encode the viral ion channel M2 (reviewed here 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…VP40 detachment from viral envelope is caused by a disruption of electrostatic interactions between VP40 and negatively charged lipids in the viral envelope, which have experimentally been demonstrated and attributed to a basic patch of lysine residues decorating the VP40 C-termini [48][49][50][51] . Considering that matrix protein assembly of other RNA viruses relies on electrostatic interactions with negatively charged lipids 60 , we propose that pH-mediated matrix disassembly is a general mechanism critical for viral uncoating. Notably, pH-driven structural remodeling of viruses has so far only been shown and extensively studied for influenza A virus 61 , which is known to encode the viral ion channel M2 (reviewed here 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Viruses generally have a membrane structure to keep the nucleic acids inside the viral vesicle. Consequently, studies have focused on the membrane proteins that mediate cell binding (such as spike protein gp120) and viral membrane proteins (such as matrix protein and envelope protein E). Choi et al studied the dynamics of the fully glycosylated full-length spike protein of SARS-CoV-2 anchored in a viral lipid bilayer. , Spike protein is important for host cell entry by binding to ACE2 protein in the host cell membrane. MD simulations reveal the spike protein orientation and dynamics characterized by rigid bodies of different parts (Figure D).…”
Section: Membrane Protein Simulationsmentioning
confidence: 99%
“…Recently, it was reported that Paramyxovirus Nipah and Measles M proteins interact with negatively charged PS lipids, and that PI(4,5)P2 significantly enhances this interaction (29).…”
Section: Pi(4 5)2 Is Not Required and Cholesterol Negatively Affects ...mentioning
confidence: 99%
“…In vitro studies have shown that RSV M protein interacts with lipid monolayers with neutral lipid compositions (DOPC/DPPC/cholesterol and DOPC/SM/cholesterol), and this interaction does not appear to be affected by the hydrophobic effect or the presence of cholesterol (28). More recent research has revealed that a specific set of lipids is required for M protein lattice formation in some paramyxoviruses, such as Nipah and measles (29). These viruses require phosphatidylserine (PS) and phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2) for M protein interaction with lipids and M protein oligomerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation